Kebijakan Krimimnal Perbuatan Ujaran Kebencian (Hate Speech) Melalui Media Sosial Menurut Hukum Pidana - Noija, Jofransly Imanuel; Toule, Elsa Rina Maya; Latumaerissa, Denny (PATTIMURA Law Study Review, 2024)
ABSTRACT: Hate speech is a prohibition stipulated in Article 28 Paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions which prohibits everyone from spreading hate speech. This act is an unlawful act because it violates human rights, such actions can be carried out not only directly but also on social networks which make people freely criticize and express hatred. Therefore, this paper aims to review and analyze the acts and forms of hate speech through social media. The research method used in this writing is Normative Juridical, the problem approach used is a statutory approach, case approach, and conceptual approach, the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The procedure for collecting legal materials in this writing is carried out by the literature study method, the processing of legal materials in this writing is carried out by systematizing legal materials by carrying out the selection of legal materials and the analysis used in this writing uses a qualitative analysis method. Based on the results of the research, it is explained that the criminalization of hate speech through social media is an act that violates the law and can be subject to criminal sanctions, the provisions regarding hate speech in Indonesia that exist at this time as stated in Articles 156, 157, 310, 311 of the Criminal Code, Article 28 jis Article 45 paragraph (2) of the ITE Law, and Article 16 of Law Number 40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination, have clearly regulated the prohibited acts and criminal threats. Hate speech crimes take several forms such as insults, defamation, blasphemy, unpleasant actions, provoking, inciting, and spreading false news on social media that cause actions that violate the rule of law.